The influence of religiosity, service, and premium rates on customer satisfaction through the sharia insurance decision as an intervening variable at Askrida Syariah Insurance Company Medan Branch - Radianti, Ami; Rahmani, Nur Ahmadi Bi; Syarbaini, Ahmad Muhaisin B. (Universitas Islam Indonesia, 2023)
IntroductionCustomer satisfaction is important aspect for an insurance company, including sharia, to succeed. For sharia insurance company many factors can lead to customer satisfaction including religiosity.ObjectivesThis research aims to analyze the influence of religiosity, service and premium rates on customer satisfaction with sharia insurance purchasing decisions as an intervening variable at the Askrida Syariah insurance company, Medan Branch. MethodThis research method is a path analysis method with a quantitative approach. The population in this study were customers who joined the Medan Branch of the Askrida Syariah Insurance Company. Samples were taken at random (random sampling) by distributing questionnaires to 100 respondents of Askrida Syariah insurance customers, Medan Branch, using the Slovin formula. The data collection method uses two approaches, namely the library approach and distributing questionnaires. The data analysis technique used in this approach is PLS with the SmartPLS program Version 3.2.8.ResultsThe research results show that religiosity and service have a positive and significant impact on customer satisfaction, while premium rates have a negative and insignificant impact. Religiosity and service have a negative and insignificant effect on customer satisfaction through sharia insurance decisions, while premium rates have a positive and significant effect. ImplicationsInsurance companies need to increase customer satisfaction, this can be done by building the concept of religiosity, especially sharia insurance, this is done to increase customer and prospective customer trust in the insurance program provided.Originality/NoveltyThis research contributes to the development of the sharia insurance business which prioritizes the dimensions of religiosity, service and premium rates.